CRITIQUE OF A WOMAN FACING REALITY OR DEAL CONDITION AS REFLECTED IN DANIELLE STEELâ€™S NOVEL â€œDADDYâ€ - Savitri, Yulidar Nur (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2013)
This study is about a woman who is influenced by womenâ€™s liberal movement which is reflected by the main character who is represented in the novel â€œDaddyâ€. The objectives of this study are to find out what is the view of being educated described in the novel and the changing role of women in society. This research is descriptive qualitative. The main source of this study is the Danielle Steelâ€™s novel Daddy. The data were taken in the form of phrases, sentences, paragraphs, and dialogues from the novel. The data were collected by doing reading, identifying, classifying, selecting, analyzing, and reporting them. The data were analyzed usingÂ  structuralismÂ  theory.Â  Theory of structuralism was used for analyzing the character of Sarah Watson as the main role. From the data analysis, I may conclude that 1) Daddy novel reflected the life of women in around 1960s to 1980s. It is the time when women get the opportunity in getting higher education after World War II and women movements. And as being educated, women could get a job and be equal with men. 2) Daddy novel is a simple reflection of the influence of women movement. By the characters, Steel describes the women issue in that time clearly. The women issue as the main issue in women movement such as freedom of choice to vote, apply for employment, use of hotels, restaurants, getting higher educationÂ  and all other public places. Those issues are the main things which women movement strugle for and it also led the changing of women role in society in that time.